Le Saint-Laurent, pivot du système défensif de Québec (1757-1759) - Noël, Dave (The Northern Mariner / Le marin du nord, 2011)
Anticipating the possible siege of Quebec, General Montcalm's staff started in 1757 to elaborate a defence system of the estuary of the St. Lawrence, a project which one can divide into two operational sectors: the Laurentian channel and the Quebec basin. In this article, the author examines the fundamentals of the French defensive system as well as the factors which contributed to its partial application in the spring of 1759. « Je ne vois nulle part aucune armée qui se soit trouvée dans une position exactement semblable à la nôtre. Nous sommes assiégés par terre et par l’eau et nous sommes obligés de pourvoir à la défense d’une ville qui n’a pour toute ressource qu’une nombreuse artillerie. Une armée de terre nous observe, tandis qu’une flotte nous côtoye et influe par son approche à faire pencher la balance à notre désavantage. »